Analysis of overtaking patterns of Indian drivers with data collected using a LiDAR. (October 2020) - Soni, Rahul; Vasudevan, Vinod; Dutta, Bhupali
Highlights: Overtaking maneuvers are not well studied in low- and middle-income countries. The traffic has high vehicle heterogeneity and drivers exhibit poor lane discipline. This study used LiDAR and video data. Overtaking is influenced by the properties of overtaking and overtaken vehicles. Side of overtaking has a strong influence in overtaking time. Abstract: Vehicle overtaking is a complex maneuver on highways and high-speed arterials. When overtaking occurs in heterogeneous traffic conditions, it becomes even more challenging due to the variety of different vehicle sizes and operating characteristics. This study analyzes overtaking behavior on Indian highways under high vehicle heterogeneity. Data were collected using LiDAR and video cameras from an instrumented vehicle. Overtaking times for both sides of overtaking and for different types of vehicles were analyzed. This study introduces a new variable, "excess distance, " to understand overtaking. The results show that on divided four-lane roads, the side of overtaking plays an important role in determining overtaking behavior. On undivided two-lane roads, the type of overtaken vehicle is found to be significant. It is observed, as expected, that while overtaking at higher speeds, overtaking vehicles maintained greater excess distances with the overtaken vehicle. However, data shows that the rate of change of excess distance depends upon the type of road and the type of overtaking vehicle. The analysis also shows that overtaking behavior on undivided roads is affected by the presence of oncoming vehicles and the type of overtaken vehicle.